The Influence of Tax Planning, Debt Policy and Information Transparency on Company Value - Siti Dalpa Adawiyatun Nisa; A. Asrorudin (International Journal of Educational and Life Sciences, 2024)
This study aims to explore the relationship between debt policy, tax planning, and information transparency and corporate value. This study used a quantitative descriptive model and secondary data from the company's annual financial records. The study's population consists of real estate and property companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The samples were selected using purposive sampling, and 45 data points from nine organizations that were monitored for five years were obtained. The panel data regression technique is used as a data analysis tool in this paper. The results showed that tax planning, debt policy, and information transparency all simultaneously affect firm value. The worth of Therefore, partial tax planning and transparency have no effect on the company, whereas debt policy has a partial impact on firm value.